2017
DOI: 10.1038/s41598-017-12255-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between polymorphisms of the NR3C1 gene and glucocorticoid effectiveness in patients with pemphigus vulgaris

Abstract: AbstractsGlucocorticoid (GC) resistance is the major obscule in the treatment of pemphigus vulgaris (PV) for both patients and clinicans with unclear mechanism. A hypotheis for this resistance is the mutations or polymorphisms present in the nuclear receptor subfamily 3, group C, member 1 (NR3C1) gene that encodes receptors for steroid hormones. This study aimed to investigate the association between NR3C1 gene polymorphisms and GC effectiveness in PV patients. 94 PV patients (64 GC-sensitive and 30 GC-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
3
14
2
Order By: Relevance
“…None of the 15 PV patients exhibited the rs6189, rs6190, rs6195, or rs6198 SNPs associated with GC e cacy in patients with in ammatory bowel disease and rheumatoid arthritis [10], [11], [12], [15]; our sample size may have been too small. A Chinese study found signi cant relationships between rs17209237, rs11745958, rs33388, and rs7701443 and GC e cacy in PV patients [17]. We also identi ed these SNPs; the genotype and allele frequencies were similar to those in Chinese patients.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…None of the 15 PV patients exhibited the rs6189, rs6190, rs6195, or rs6198 SNPs associated with GC e cacy in patients with in ammatory bowel disease and rheumatoid arthritis [10], [11], [12], [15]; our sample size may have been too small. A Chinese study found signi cant relationships between rs17209237, rs11745958, rs33388, and rs7701443 and GC e cacy in PV patients [17]. We also identi ed these SNPs; the genotype and allele frequencies were similar to those in Chinese patients.…”
Section: Discussionmentioning
confidence: 75%
“…We found correlations between three SNPs (rs17209237, rs117458958, and rs6196) and the clinical response to GCs. rs17209237 and rs117458958, located in introns, were rst shown to correlate with GC e cacy in PV patients by Fang et al [17]. However, of the 17 SNPs for each position in LD (r 2 > 0.8) in the CHB and JPT populations, none was predicted to be functional; further research is needed.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations